The labor market in Switzerland, 2000-2018 - Rafael Lalive; Tobias Lehmann (IZA World of Labor, 2020)
Switzerland is a small country with rich cultural and geographic diversity. The Swiss unemployment rate is low, at around 4%. The rate has remained at that level since the year 2000, despite a massive increase in the foreign labor force, the Great Recession, and a currency appreciation shock, demonstrating the Swiss labor market's impressive resiliency. However, challenges do exist, particularly related to earnings and employment gaps between foreign and native workers, as well as a narrowing but persistent gender pay gap. Additionally, regional differences in unemployment are significant.
Keywords: 330; unemployment; real earnings; labor force participation; Switzerland